Global Crisis Financial Policies - Nimani, Artan; Rezniqi, Shpetim; Valbona Zeqira; Zogu, Nevruz (European Journal of Social Science Education and Research, 2022)
The current crisis has swept the world with special emphasis, most developed countries, those countries which have most gross -product world and you have a high level of living. Even those who are not experts can describe the consequences of the crisis to see the reality that is seen, but how far will it go this crisis is impossible to predict. Even the biggest experts have conjecture and large divergence, but agree on one thing:- The devastating effects of this crisis will be more severe than ever before and can not be predicted. Long time, the world was dominated economic theory of free market laws. With the belief that the market is the regulator of all economic problems. The market, as river water will flow to find the best and will find the necessary solution best. Therefore much less state market barriers, less state intervention and market itself is an economic self regulation.
Keywords: global crisis, financial policies, free market, economic problems